A Computational Model for Simulation of CO2 Corrosion Rate along Pipelines - Mohyaldinn, Mysara Eissa; El-Khatib, Noaman A.F.; Ismail, Mokhtar C (2010)
Carbon dioxide (CO2) may be contained in the oil and gas as a light impurity or it may be injected in the reservoir during enhanced oil recovery (EOR). The presence of CO2 with water in oil transported through a steel pipe forms a suitable environment for corrosion initiation. The corrosion propagates depending on the flow and chemical properties such as velocity, temperature, CO2 partial pressure, and pH. At certain instant, a protection layer consists of iron carbonate is formed on the pipe surface. This layer protects the steel from subsequent attack and decreases the corrosion rate. In the case of simultaneous presence of sand with CO2, continuous impingements of the sand will remove the protection layer and lead to the so-called erosion-corrosion.